Pragmatic development in a foreign language: A study of Greek FL requests - Spyridoula Bella (Journal of Pragmatics, 2012)
This study investigates developmental patterns in the requestive behavior of foreign language learners of Greek. Drawing data from a DCT it attempts to explore the head acts and external/internal modification devices that learners of three different proficiency levels (lower intermediate, intermediate and advanced) employ when performing requests in one formal (+P, +D) and two informal (−P, −D) situations. The results suggest that although several aspects of the learners’ pragmatic competence develop with increasing proficiency, even the advanced learners’ performance lags far behind native speakers in several respects. Furthermore, it is shown that these learners’ behaviors lend considerable support to both the developmental stages of pragmatic competence acknowledged in the relevant literature (0125 and 0005) and to Bialystok's model regarding the acquisition of pragmatic competence. What is more, it lends a great deal of cross-linguistic validity to earlier finding regarding the development of requests in the interlanguage of FL learners.